2014
DOI: 10.1021/es500804g
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Ferrate(VI) with ABTS and Self-Decay of Ferrate(VI): Kinetics and Mechanisms

Abstract: Reactions of ferrate(VI) during water treatment generate perferryl(V) or ferryl(IV) as primary intermediates. To better understand the fate of perferryl(V) or ferryl(IV) during ferrate(VI) oxidation, this study investigates the kinetics, products, and mechanisms for the reaction of ferrate(VI) with 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonate) (ABTS) and self-decay of ferrate(VI) in phosphate-buffered solutions. The oxidation of ABTS by ferrate(VI) via a one-electron transfer process produces ABTS(•+) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
238
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(252 citation statements)
references
References 47 publications
14
238
0
Order By: Relevance
“…At pH 7.5 and 6.2, the apparent reaction constant is faster than the maximum detectable rate of the stopped flow system, 9 Â 10 4 M À1 s À1 . This reaction rate constant is orders of magnitude larger than the reaction rate constant of ferrate self-decay of 1 Â 10 2 M À1 s À1 and 2 Â 10 2 M À1 s À1 , at pH 7.5 and 6.2, respectively (Lee et al, 2014). This supports the conclusion that ferrate self-decay is not appreciable in the stoichiometry of Mn(II) oxidation.…”
Section: Reaction Kineticssupporting
confidence: 72%
See 1 more Smart Citation
“…At pH 7.5 and 6.2, the apparent reaction constant is faster than the maximum detectable rate of the stopped flow system, 9 Â 10 4 M À1 s À1 . This reaction rate constant is orders of magnitude larger than the reaction rate constant of ferrate self-decay of 1 Â 10 2 M À1 s À1 and 2 Â 10 2 M À1 s À1 , at pH 7.5 and 6.2, respectively (Lee et al, 2014). This supports the conclusion that ferrate self-decay is not appreciable in the stoichiometry of Mn(II) oxidation.…”
Section: Reaction Kineticssupporting
confidence: 72%
“…In other reactions, Fe(VI) may undergo a one or two electron transfer, momentarily resulting in perferryl(V) or ferryl(IV) (Lee et al, 2005;Sharma, 2010). These intermediates are much more reactive than Fe(VI), and may react rapidly and indiscriminately with other solutes, including H 2 O (Lee et al, 2014). The production of these intermediates is difficult to Fig.…”
Section: Stoichiometry In Laboratory Water Matrixmentioning
confidence: 99%
“…Figure 2 includes the results from experiments up to the previously described optimal Fe(VI) dose of 25 μM, in terms Fe and Mn precipitated on a molar basis. Figure 2 also includes the theoretical stoichiometry of the oxidation reaction between Fe(II) and Fe(VI) (Lee et al, 2014), and Mn(II) and Fe(VI) (Goodwill et al, 2016b), respectively. Lee et al (2014) demonstrated a 3:1 stoichiometry in an N 2 –purged, circumneutral pH solution with 5 mM carbonate buffer (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that Fe(VI) auto‐decay (e.g., oxidation of water) competes with other redox pathways, or that the Fe and Mn were already in an oxidized state prior to Fe(VI) addition. The apparent rate constant ( k app ) of Fe(VI) auto‐decay has been quantified by Lee et al (2014) and ranges from ∼5 × 10 4 M −1 s −1 at pH 3.0 to ∼1 × 10 4 M −1 s −1 at pH 3.5. However, Lee et al used phosphate buffers to sequester Fe(III) iron particles, which retards the rate of Fe(VI) decay (Jiang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The direct ultraviolet (UV) absorbance method, the iodometric method, the DPD method, a membrane electrode method and the indigo method are those most commonly used for determination of aqueous ozone in the laboratory. Although these methods have been used for ozone determination for many years, there are still significant disadvantages that limit their application (Lee, Kissner, and Von Gunten 2014;Von Gunten 2003b).…”
Section: Introductionmentioning
confidence: 99%